A preliminary comparison of cranial and external morphological variability of Southern Crested Newt (Triturus karelinii) from the Crimea and the Caucasus - Pysanets, Y.; Kukushkin, O.; Manuilova, O. (Збірник праць Зоологічного музею, 2014)
The Triturus karelinii group of crested newts comprises the eastern, central and western lineages that differ by mitochondrial DNA. The eastern lineage largely retains the ancestral cranium shape and is distributed throughout the Crimean Peninsula, the Caucasus Isthmus, and the Caspian Sea southern shore in Iran. In this report the comparison of the Crimean and Trascaucasian T. karelinii cranium shape, differences in the dimensional characteristics variability and body colouring patterns is presented. The samples of T. dobrogicus from the Danube River Delta have been employed for outgroup comparison. Data of the differences between several populations within the eastern lineage suggest that it is not uniform and T. karelinii from the Crimean Peninsula is considered to be somewhat different.